Chandra observations of the planetary nebula IC 4593. Issue 3 (21st April 2020) - Toalá, J A; Guerrero, M A; Bianchi, L; Chu, Y-H; De Marco, O
ABSTRACT: The Advanced CCD Imaging Spectrometer (ACIS-S) camera on board the Chandra X-ray Observatory has been used to discover a hot bubble in the planetary nebula (PN) IC 4593, the most distant PN detected by Chandra so far. The data are used to study the distribution of the X-ray-emitting gas in IC 4593 and to estimate its physical properties. The hot bubble has a radius of ∼2 arcsec and is found to be confined inside the optically bright innermost cavity of IC 4593. The X-ray emission is mostly consistent with that of an optically thin plasma with temperature kT ≈ 0.15 keV (or T X ≈ 1.7 × 10 6 K), electron density n e ≈ 15 cm −3, and intrinsic X-ray luminosity in the 0.3–1.5 keV energy range L X  = 3.4 × 10 30 erg s −1 . A careful analysis of the distribution of hard ( E >0.8 keV) photons in IC 4593 suggests the presence of X-ray emission from a point source likely associated with its central star (CSPN). If this was the case, its estimated X-ray luminosity would be L X, CSPN  = 7 × 10 29  erg s −1, fulfilling the log( L X, CSPN / L bol ) ≈ −7 relation for self-shocking winds in hot stars. The X-ray detection of the CSPN helps explain the presence of high-ionization species detected in the ultraviolet spectra as predicted by stellar atmosphere models.